PENERAPAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) UNTUK MENGEVALUASI KINERJA MESIN-MESIN DI STASIUN GILING PABRIK GULA KREBET II MALANG - Lu'lu Ul Maknunah, Fuad Achmadi, dan Retno Astuti (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Sugar Factory Krebet Baru II Malangwas facing increased down time up to 66.64% from the previous production period with the highest down time at milling station. A machine effectiveness measurement was used to valuate machine performance. The objectives of this research were to evaluate the performance of machines in the milling station using OEE (Overall Equipment Effectiveness) and to find factors that most influence the OEE value with six big losses method. OEE was gained by multiplying the value of availability, performance rate and quality rate. The results of the research showed that OEE value of each machine were between 70.52-78.81%. The OEE values didnot reach the ideal value, which was 85%.The factor that most influenceof OEE value was reduced speed loss factor with value from 49.67% to 63.50%.Keywords: machine performance measurement, milling station, OEE, six big losses